Analisis Penilaian Aset Tetap Berdasarkan Pernyataan Standar Akuntansi Pemerintahan (PSAP) No. 07 Tahun 2010 pada Desa Suka Damai Kecamatan Muara Badak - Fitriani; Wulaningrum, Ratna; Fitriana, Rahmawati (Politeknik Negeri Samarinda, 2024)
This research aims to find out whether the valuation of fixed assets in Suka Peace Village, Muara Badak District is in accordance with government accounting standard statements. The research uses a comparative descriptive method with a qualitative approach to describe and compare fixed asset assessment implementation activities. Data collection techniques are carried out by observation, namely direct observation in the field, interviews, documentation. Data analysis techniques by collecting data, describing, comparing and concluding. The analytical tool used is PSAP methodology number 07 of 2010 concerning fixed assets. The results of this research show that the recognition of fixed assets in the form of buildings and structures, village office equipment, motorbikes and ambulances has been implemented in accordance with PSAP number 07 concerning fixed assets and the opinions of informants in Suka Peace Village, Muara Badak District. The measurement of fixed assets in the form of buildings and structures, village office equipment, motorbikes and ambulances has been implemented in accordance with PSAP number 07 concerning fixed assets and informant opinions in Suka Peace Village, Muara Badak District. As well as disclosure of fixed assets in the form of buildings, village office equipment, motorbikes and ambulances, it has been implemented in accordance with PSAP number 07 concerning fixed assets and informant opinions in Suka Peace Village, Muara Badak District. However, village office buildings and structures are currently not village property, and are still in the stage of applying for village ownership and ownership rights.